Killer Facebook ads master cutting-edge Facebook advertising techniques - Weintraub, Marty, 1959- (San Francisco : John Wiley & Sons, Inc., 2011)
"Expert Facebook advertising techniques you won't find anywhere else!Facebook has exploded to a community of more than half a billion people around the world, making it a deliciously fertile playground for marketers on the cutting edge. Whether you want to leverage Facebook Ads to generate "Likes," promote events, sell products, market applications, deploy next-gen PR, ,this unique guide is the ultimate resource on Facebook's wildly successful pay-per-click advertising platform. Featuring clever workarounds, unprecedented tricks, and little-known tips for triumphant Facebook advertising, it's a must-have on the online marketer's bookshelf. Facebook advertising expert Marty Weintraub shares undocumented how-to advice on everything from targeting methods, advanced advertising techniques, writing compelling ads, launching a campaign, monitoring and optimizing campaigns, and tons more.Killer Facebook Ads serves up immediately actionable tips & tactics that span the gambit. Learn what Facebook ads are good for, how to set goals, and communicate clear objectives to your boss and stakeholders. Master highly focused demographic targeting on Facebook's social graph. Zero in on relevant customers now. Get extraordinary advice for using each available ad element--headline, body text, images, logos, etc.--for maximum effect How to launch a Facebook advertising campaign and crucial monitoring and optimizing techniques Essential metrics and reporting considerations Captivating case studies drawn from the author's extensive Facebook advertising experience, highlighting lessons from challenges and successes Tasty bonus: a robust targeting appendix jam-packed with amazing targeting combos Packed with hands-on tutorials and expert-level techniques and tactics for executing an effective advertising campaign, this one-of-a-kind book is sure to help you develop, implement, measure, and maintain successful Facebook ad campaigns"--
Includes index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Facebook (Electronic resource); Internet advertising; Electronic books